Synthesis and structural characterisation of cationic, neutral and hydroxo-bridged lanthanoid (La, Gd, Ho, Yb, Y) bis 5-(2-pyridyl)tetrazolate complexes - Andrews, P.; Beck, T.; Fraser, B.; Junk, Peter; Massi, Massimiliano (PERGAMON-ELSEVIER SCIENCE LTD, 2007)
Reaction of an excess of hydrated LnCl(3) (Ln = La, Gd, Ho, Yb, Y) with sodium 5-(2-pyridyl)tetrazolate (Napytz) in water led to the formation of either cationic disubstituted complexes (La, Gd, Ho) or neutral g-hydroxo-bridged dimers (Y, Yb). Interestingly, there is a lack of propensity for these disubstituted complexes to redistribute forming trisubstituted ones, which is a common behaviour in lanthanoid chemistry. Also, compared to their corresponding lanthanoid carboxylates, all these products are discrete molecular entities forming an extensive hydrogen-bonded and/or pi stacking network rather than hybrid polymeric frameworks.